Sodium Transporters in Human Health and Disease - Gagnon, Kenneth B.; Delpire, Eric (Frontiers in Physiology, 2021)
Sodium (Na+) electrochemical gradients established by Na+/K+ ATPase activity drives the transport of ions, minerals, and sugars in both excitable and non-excitable cells. Na+-dependent transporters can move these solutes in the same direction (cotransport) or in opposite directions (exchanger) across both the apical and basolateral plasma membranes of polarized epithelia. In addition to maintaining physiological homeostasis of these solutes, increases and decreases in sodium may also initiate, directly or indirectly, signaling cascades that regulate a variety of intracellular post-translational events. In this review, we will describe how the Na+/K+ ATPase maintains a Na+ gradient utilized by multiple sodium-dependent transport mechanisms to regulate glucose uptake, excitatory neurotransmitters, calcium signaling, acid-base balance, salt-wasting disorders, fluid volume, and magnesium transport. We will discuss how several Na+-dependent cotransporters and Na+-dependent exchangers have significant roles in human health and disease. Finally, we will discuss how each of these Na+-dependent transport mechanisms have either been shown or have the potential to use Na+ in a secondary role as a signaling molecule.